Can Disaster Risk Education Reduce the Impact of Disasters in Schools? - Mulianingsih, Ferani; Hardati, Puji (Journal of Geography Science and Education, 2022)
One of the largest cities in Indonesia is Semarang City. This city has a very high level of disaster proneness. The following are disasters that often occur in the city of Semarang, including floods, tidal waves, landslides, and droughts. The impact of repeated disasters on urban communities is damage and loss of life. However, currently disaster risk education introduces risk mitigation and disaster preparedness in minimizing the impact of disasters in urban areas. Disaster risk reduction has been included in the school curriculum. The purpose of writing this article is to examine the role of schools in disaster mitigation, disaster curriculum in schools. Empowering school-age children to understand disaster mitigation is the first step in building a disaster-aware community. So that when a disaster occurs, people no longer experience confusion and panic, because they have understood how to reduce disaster risk. School-age children are expected to be able to bring the knowledge they have learned from school and become "agents" who can build a culture of disaster awareness in their environment, so that a resilient society can be realized in dealing with disasters.